Distribution of the vibration effect within the stacked boxes during vehicular road transportation of tomatoes - Ranatunga, C.L.; Jayaweera, H.H.E.; Suraweera, S.K.K.; Ariyaratne, T.R. (University of Sri Jayewardenepura, 2014)
Attached

Parameters of the Road-Vehicle—Load system influence the vibration effects generated at vehicular road transportation. Vertical vibration acceleration (PSDmax) experienced by the tomato boxes and tomatoes within the box was studied using the popular transport means in lllukkumbura area in Matale. The road quality was estimated using the International Road Roughness Index (lRl). Fully loaded Mitsubishi Canter truck at an average speed of 20 kmh'l on a road rated at lRl between 2 to 3.5 mm/m registered increasing trend in the PSD of vibration from the front side towards the rear side of the truck in the horizontal direction. The observed average PSD values are in the approximate ratio, front : middle : rear 2 l : 3: 6. Also the PSD of the vibration was found to be amplified from the bottom stack towards the topmost stack in the vertical direction. The observed average PSD values at 1“, 2nd, 3‘“, and 41h stacks are in the approximate ratio, 1 : l : l.5 : 2.5. PSD of vibration was studied with a fully loaded truck at different speeds on a road consisting of segments rated at varying RI. The fully loaded truck at different speeds on a road consisting of segments rated at varying lRl registered varying PSD values of vibration. Even at lower speeds such as 25 kmh'I the vibration acceleration produced at “poor” quality (lRl > 5 mm/m) roads was nearly 4 times higher compared to that produced at “fair" URI 2 to 3.5 min/m) or “good” quality (1R1 0.9 to 2 mm/m) roads. Registered pattern of the PSD appears to be similar at the tomato boxes and at the tomatoes within the same box.
Keywords: Vehicular Road transportation; Vehicular vibration; Power spectral density of vibration; Road-vehicle-load system; Road roughness; Stacked cargo